Molecular characterization of Votho pigs from Nagaland using microsatellite markers - ZAMAN, G; SHEKAR, M CHANDRA; NATH, M K; KIBA, H Z; SAVINO, N (The Indian Journal of Animal Sciences, 2014)
This study details genetic diversity of Votho pig population using a set of 21 microsatellite markers recommended by Food and Agriculture Organization of United Nations (FAO) for Swine. All the studied loci were highly informative. The number of observed alleles (Na) detected ranged from 2 to 10, with an overall mean of 5.59±0.598. In total 122 alleles were observed across the investigated loci. The effective number of alleles (Ne) ranged from 1.054 to 5.075 with a mean of 3.02±0.284. The Polymorphic Information Content (PIC) value ranged from 0.0499 to 0.7750 with the overall mean of 0.53±0.250. The overall means for observed (Ho) and expected (He) heterozygosities were 0.38±0.060 and 0.57±0.055 respectively. The within breed inbreeding estimate indicated heterozygosity shortage of 0.273. The Hardy-Weinberg equilibrium (HWE) test revealed that 14 out of 21 loci deviated from equilibrium. Shannon’s information index (I), was sufficiently high with a mean of 1.17±0.124. The bottleneck analysis revealed that population has not undergone any recent reduction.